United States and Caribbean strategies : three assessments - Bernal, Richard L. (CSIS Americas Programme WashingtonUS, 2001)
Highlights the trends and prospects for US-Caribbean relations at the dawn of a new era of hemispheric integration. Focuses on the Caribbean's position in the new global economy, US-Caribbean relations from the Caribbean perspective, and US policy toward the region.